THE UTILIZATION OF ZOOM, GOOGLE CLASSROOM, AND QUIZIZZ IN MARITIME ENGLISH LEARNING - Angga Aminullah Mansur; Dian Nur Asmawati (University of Kuningan, 2021)
This current pandemy has led both educators and students to acquire the ability to vastly adjust themselves in picking out and applying both a suitable and convinient way of teaching and learning that involve the use of technology. This paper is aimed at describing (1) how online learning platforms namely Zoom, Google Classroom, and Quizizz are collaboratively utilized in Maritime English (ME) learning (2) how effective they are, and (3) what setbecks the students encounterd during the learning proscess via this collaboration. The study uses a qualitative approach in which 62 of the total numbers of 110 students were surveyed by applying a purposive sampling inquiry technique after having accomplished their ME course for about three months to find out the effectivity and setbacks of the integration of those three online learning platforms. According to the survey, it turns out that the integration of those three platforms tends to be effective to be applied for ME learning in the meantime situation with the interval scale of 83.55% (strongly agree) and respectively feel that online learning method is the best method of learning to be applied in this current pandemic situation with the interval scale of 81.61% (strongly agree). However, the scale went lower, notching only 58.71% (unsure), when the students were inquired whether the online learning method in general is suitably applied regularly in normal time. This happens due to some constrains they have as well.